Peningkatan Kualitas Kimia Tanah Sulfat Masam dengan Aplikasi Kombinasi Bahan Organik Lokal dan Limbah Agroindustri - Muhammad Helmy Abdillah; Dewi Amelia Widiyastuti (Institut Pertanian Bogor, 2022)
The purpose of this research was to assess effect of compost treatment from various local organic materials combined with agro-industrial waste to improved chemical quality of acid sulfate mineral soils, to compare of root dry weight and grain weight milled dryness of Inpara-3. This research was conducted at screen house of Polytechnic Hasnur, Barito Kuala District, South Kalimantan from November 2020 to June 2021. This study used Compeletely Randomized Design (CRD) with Tukey's Honestly Significant Difference (HSD) test a=5%. There were 7 treatments used as, K0 = control. JKD = paddy straw compost 4 t ha-1 and solid decanter 2 t ha-1; JKR = paddy straw compost 4 t ha-1 and solid crumb rubber 2 t ha-1; SKD = empty fruit bunch compost 4 t ha-1 and solid decanter 2 t ha-1; SKR = empty fruit bunch compost 4 t ha-1 and solid crumb rubber 2 t ha-1; PKD = compost of purun tikus (Eleocharis dulcis) 4 t ha-1 and solid decanter 2 t ha-1; PKR = compost of purun tikus 4 t ha-1 and LPKR 2 t ha-1. The treatment was 5 replication so that 35 experimental plant units. The results showed compost paddy straw combinated solid decanter reducing concentration of soluble Fe and Al and can increasing availability of P and K. Treatment of compost empty fruit bunch combinated solid decanter can be increasing pH and total N-mineral. Compost paddy straw combinated solid crumb rubber gave increasing weight on root dry and grain milled dryness. Keywords: acid sulfate soil; agroindustrial wasted; compost